Reconstructing the range expansion of the European starling in Southern Africa using a hybrid method of niche modelling and individual based modelling - Janse van Rensburg, Marinel (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.